2005
DOI: 10.1093/nar/gni151
|View full text |Cite
|
Sign up to set email alerts
|

End invasion of peptide nucleic acids (PNAs) with mixed-base composition into linear DNA duplexes

Abstract: Peptide nucleic acid (PNA) is a synthetic DNA mimic with valuable properties and a rapidly growing scope of applications. With the exception of recently introduced pseudocomplementary PNAs, binding of common PNA oligomers to target sites located inside linear double-stranded DNAs (dsDNAs) is essentially restricted to homopurine–homopyrimidine sequence motifs, which significantly hampers some of the PNA applications. Here, we suggest an approach to bypass this limitation of common PNAs. We demonstrate that PNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 63 publications
0
20
0
2
Order By: Relevance
“…16 Dabcyl was used as quencher, linked to the e-amino group of lysine at the C-terminal part and carboxyfluorescein was used as fluorophore, linked to the N-terminus of the PNA molecule; two additional charges (a positive arginine side chain and a negative glutamate unit) were inserted just before and after the PNA segment, according to the design described by Frank-Kamenetskii and coworkers. 16,17 Arginine was used instead of lysine as originally proposed, in order to avoid any possible competition with the side chain amino group of the chiral monomer during attachment to a solid support or micro-and nanoparticles. Recent studies carried out in our laboratory have shown that substitution of the achiral N-(2-aminoethyl) amino acid backbone with chiral units derived from amino acid can affect the DNA binding ability depending on the position and the stereochemistry of the stereogenic centers introduced.…”
Section: Results and Discussion Beacon Design And Chiral Monomer Syntmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Dabcyl was used as quencher, linked to the e-amino group of lysine at the C-terminal part and carboxyfluorescein was used as fluorophore, linked to the N-terminus of the PNA molecule; two additional charges (a positive arginine side chain and a negative glutamate unit) were inserted just before and after the PNA segment, according to the design described by Frank-Kamenetskii and coworkers. 16,17 Arginine was used instead of lysine as originally proposed, in order to avoid any possible competition with the side chain amino group of the chiral monomer during attachment to a solid support or micro-and nanoparticles. Recent studies carried out in our laboratory have shown that substitution of the achiral N-(2-aminoethyl) amino acid backbone with chiral units derived from amino acid can affect the DNA binding ability depending on the position and the stereochemistry of the stereogenic centers introduced.…”
Section: Results and Discussion Beacon Design And Chiral Monomer Syntmentioning
confidence: 99%
“…Achiral PNA beacons have been successfully used in many applications and have shown a strong discrimination ability between full matched and single mismatched DNA sequences; 16,17 however, it was interesting to verify if the selectivity in recognizing single-point mutations could be further improved by the presence of a stereogenic center in the backbone. The hybridization properties of the chiral PNA beacon were examined using UV melting temperatures and compared with those observed with the achiral unmodified beacon (Table 1).…”
Section: Uv Melting Temperatures Of Chiral and Achiral Pna Beaconsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though promising as antigene reagents, because of the specificity of recognition and generality in sequence design, PNA binding is presently limited to mostly homopurine [22] and homopyrimidine targets. [23] Mixed-sequence PNAs have been shown to be capable of invading topologically constrained supercoiled plasmid DNA, [24][25][26][27] conformationally perturbed regions of genomic DNA [28] and duplex termini; [29] however, they are unable to invade the interior regions of double helical B-form DNA (B-DNA)-the most stable form of DNA double helix. "Tail-clamp" [30,31] and "doubleduplex invasion" [32] strategies have subsequently been developed and have enabled mixed-sequence PNAs to invade B-DNA, but they are not without limitations.…”
mentioning
confidence: 99%
“…More recently, we showed that sequence restriction can be relaxed by utilizing conformationally preorganized γPNAs as molecular reagents (Chart 1a, bottom) (19). However, like all the other studies, with the exception of triplex-binding by homopyrimidine PNAs (20), strand invasion of linear double helical B-DNA was performed in buffers containing relatively low salt concentrations (11, 18, 19, 21, 22). When subjected to physiological ionic strengths, little to no binding was observed (23).…”
mentioning
confidence: 99%